Är likadelningsprincipen likställd med jämställdhet? - En studie av likadelningsprincipens ändamålsenlighet ur ett jämställdhetsperspektiv - Persson,Matilda (2022)
The main purpose of this essay is to study how the principle of equal division and it´s modifications have been formed and how they interact considering the aim towards gender equality that was pronounced during the legislative preparations. Furthermore, the purpose of this essay is to analyze whether the legislation is in accordance with the aim towards gender equality, considering the development of the society and the alternative property systems that were discussed in the legislative preparations and are discussed in the legal literature. The main rule of the division of property in case of legal separation is equal division, 11 chap. 3 § Swedish Marriage Code. The equal division includes the value of the property of each spouse incase no other agreement has been made, the so-called marital property, 7 chap. 1 § Swedish Marriage Code. This means that the marital property is extensive and that the community of property is strong in the Swedish property system. However, the chief of department and the family law experts stated that the Swedish Marriage Code should aim towards equality between women and men during the legislative preparations. As a part of this aim the law should encourage the independence of each spouse and also protect the spouse with less economic strength. The chief of department and the family law experts discussed alternative property systems during the legislative preparations. The property systems that were discussed aims to preserve the property of each spouse and ease the economic effects of marriage. However, the principle of equal division was considered the best alternative for women who as a group had less economic strength due to lower income. The principle of equal division was also considered the best alternative due to its simplicity. Instead of changing the entire property system the legislator tried to reduce irrational results of the principle of equal division through different modifications, such as adjustment of property division, 12 chap. 1 § Swedish Marriage Code. Each of these modifications reduces the amount of marital property that is subject to equal division and expresses economic independence at the expense of economic community. A modification that differs is maintenance after legal separation, 6 chap. 7 § Swedish Marriage Code. This modification gives the spouse with less economic strength more of the other spouse’s marital property and expresses economic community at the expense of economic independence. The rule of adjustment as well as the rule of maintenance are meant to be rules of exception and applied restrictively. The conclusion is that the principle of equal division is in accordance with the aim towards gender equality since the problems mentioned in legislative preparations remain, even though they have improved. The problems remain even though reforms have been made within other areas of law in order to improve them and the work towards gender equality has increased throughout the society. However, the principle of equal division is to extensive when it comes to property that a spouse has acquired before a marriage or during a marriage due to a gift, heritage or will from a third party. The extent is incompatible with the thought of encouraging the independence of each spouse in order to develop gender equality, since the property isn´t a result of the marriage. Apart from that the principle of equal division is to limited when it comes to the spouses´ pension rights. The limitation is incompatible with the thought of protecting the spouse with less economic strength in order to develop gender equality, since pension rights are in fact dependent on the normative choices made during a marriage.
Keywords: Familjerätt; Äktenskapsbalken; Giftorätt; Likadelning